2003
DOI: 10.1039/b310256d
|View full text |Cite
|
Sign up to set email alerts
|

Different thermal reactivity of a 1,2-thiaphospholo[a]phosphirane in free and metal carbonyl complexed formElectronic Supplementary Information (ESI) available: full experimental, spectroscopic and analytical data. See http://www.rsc.org/suppdata/cc/b3/b310256d/

Abstract: The W(CO)5 and Fe(CO)4 complexes of the bicyclic phosphirane 3,5,6,6-tetraphenyl-1-phospha-2-thiabicyclo[3.1.0]hex-3-ene undergo a thermal 2-phenylphosphirane --> dihydrophosphaisoindole ring expansion, while the free phosphirane suffers both a [2 + 1] cycloreversion and a fragmentation yielding a butadienyl sulfide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[10] As 3,5-diaryl-1,2-thiaphospholes are readily available [11] and the P=C bond of 1,2-thiaphospholes is an excellent cycloaddition partner, [12][13][14] we followed this route to synthesize a 6,6-diphenyl-2-thia-1-phosphabicyclo[3.1.0]hex-3-ene using diazodiphenylmethane as the cyclopropanation reagent. [15] We found that the thermal stabilities of both the phosphirane and its W(CO) 5 and Fe(CO) 4 complexes are only moderate, and that the effect of elevated temperatures is different for the free phosphirane and its metal complexes.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…[10] As 3,5-diaryl-1,2-thiaphospholes are readily available [11] and the P=C bond of 1,2-thiaphospholes is an excellent cycloaddition partner, [12][13][14] we followed this route to synthesize a 6,6-diphenyl-2-thia-1-phosphabicyclo[3.1.0]hex-3-ene using diazodiphenylmethane as the cyclopropanation reagent. [15] We found that the thermal stabilities of both the phosphirane and its W(CO) 5 and Fe(CO) 4 complexes are only moderate, and that the effect of elevated temperatures is different for the free phosphirane and its metal complexes.…”
Section: Introductionmentioning
confidence: 74%
“…[15] The uncomplexed phosphirane 1a undergoes a thermal fragmentation to yield a butadienyl sulfide (i.e., a tautomer of an alkenyl thione that is structurally analogous to 16 in Scheme 8), for which a phosphinidene cycloreversion, analogous to the one proposed above for the W(CO) 5 -complexed phosphiranes 10, has been suggested. The W(CO) 5 complexes 2, on the other hand, undergo a skeletal rearrangement (see Scheme 1) beginning with a homolytic cleavage of the phosphirane C-C bond, which is in contrast to the suggested P-C bond cleavage of 10 at elevated temperature.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…While the [1,3]-sigmatropic shift of vinylphosphiranes into phospholenes is experimentally ascertained, [45,46] there is scant precedent for this type of rearrangement with aromatics. [47] In addition, the [1,5]-sigmatropic phosphirane-phospholene rearrangement has also been observed experimentally, [43] but no precedents are known for this rearrangement with aromatics. Expectedly, 2-aminophosphindole 34 is the global minimum and can be formed directly from 33 via a hydrogen shift to nitrogen [48] with an exothermicity of 31.4 kcal mol À1 ; its bond lengths are in good agreement with those experimentally ascertained for compound 16 a in the crystal.…”
mentioning
confidence: 99%